2002
DOI: 10.1177/0146167202282005
|View full text |Cite
|
Sign up to set email alerts
|

Self-Enhancement as a Buffer Against Extreme Adversity: Civil War in Bosnia and Traumatic Loss in the United States

Abstract: In a challenge to traditional views of mental health, Taylor and Brown argued that an overly positive or enhanced perception of the self was adaptive, particularly in conditions of extreme adversity. Researchers have tempered this view with evidence linking self-enhancing biases to negative social consequences. This article reports studies examining self-enhancement in the context of civil war in Bosnia (Study 1) and premature conjugal loss (Study 2). In both studies, mental health experts rated self-enhancing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
142
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(153 citation statements)
references
References 61 publications
9
142
1
1
Order By: Relevance
“…One factor seems to be the ability to self-enhance (Bonanno, 2004)-to perceive the self as possessing more positive attributes than the average person (Taylor & Brown, 1988). In support of this claim, measured levels of self-enhancement were associated with better adjustment among Bosnian civilians after the civil war in Sarajevo (Bonanno, Field, Kovacevic, & Kaltman, 2002). In another study involving people near the World Trade Center at the time of the 9/11 terrorist attacks, self-enhancement (as assessed by endorsement of such statements as ''I am fully in control of my own fate,'' and ''I always know why I do things''; see Paulhus, 1984) prospectively predicted a reduction in both depression and in Post Traumatic Stress Disorder symptoms (Bonanno, Rennicke, Dekel, & Rosen, 2005).…”
Section: B Coping and Resiliencementioning
confidence: 87%
“…One factor seems to be the ability to self-enhance (Bonanno, 2004)-to perceive the self as possessing more positive attributes than the average person (Taylor & Brown, 1988). In support of this claim, measured levels of self-enhancement were associated with better adjustment among Bosnian civilians after the civil war in Sarajevo (Bonanno, Field, Kovacevic, & Kaltman, 2002). In another study involving people near the World Trade Center at the time of the 9/11 terrorist attacks, self-enhancement (as assessed by endorsement of such statements as ''I am fully in control of my own fate,'' and ''I always know why I do things''; see Paulhus, 1984) prospectively predicted a reduction in both depression and in Post Traumatic Stress Disorder symptoms (Bonanno, Rennicke, Dekel, & Rosen, 2005).…”
Section: B Coping and Resiliencementioning
confidence: 87%
“…As another case in point, selfenhancement is positively related to the psychological health of civilians exposed to urban combat at war time and also predicts the psychological health of widows two years later (Bonanno, Field, Kovacevic, & Kaltman, 2002) in Bosnia. More generally, high self-esteem confers vital benefits to the individual (Swann, Chang-Schneider, & McClarty, 2007), such as psychological health (Trzesniewski et al, 2006), social acceptance (Leary, Cottrell, & Phillips, 2001), and existential safety (Pyszczynski et al, 2004).…”
Section: Self-enhancement and Self-protection 33mentioning
confidence: 92%
“…While most studies have found that overconfidence is associated with self-reported wellbeing (Bonanno et al, 2002;Kwan et al, 2004;Paulhus, 1998;Robins & Beer, 2001), when adjustment is rated by independent observers, the story is much bleaker --overconfident individuals are rated as lower in adjustment by trained clinicians (though see Bonanno et al, 2002;Colvin et al, 1995;Kwan, John, Robins, & Kuang, 2008) and friends (Dufner et al, 2013;Kurt & Paulhus, 2008). This tradition has also hinted at other negative effects of overconfidence, with overconfident individuals performing worse on group assignments (Kwan et al, 2004) and overconfident military cadets achieving worse leadership evaluations (Lönnqvist, Leikas, Verkasalo, & Paunonen, 2008).…”
Section: Social Criterion Measuresmentioning
confidence: 99%
“…Examples include never having felt anger or never having sworn in one's life (Balanced inventory of desirable responding (BIDR) ;Paulhus, 1988). Studies using this measure have generally found overconfidence to be associated with positive mental health outcomes, while the association with social outcomes range from positive to negative (Bonanno, Field, Kovacevic, & Kaltman, 2002;Bonanno, Rennicke, & Dekel, 2005;Goorin & Bonanno, 2009;Gupta & Bonanno, 2010;Paulhus, 1998;Yan & Bonanno, 2015). These questionnaires reduce the problems associated with a pure positive self-perception measure, but the behaviours described are not technically impossible.…”
Section: The Measurement Of Overconfidencementioning
confidence: 99%
See 1 more Smart Citation